Tobacco-free grounds implementation in California residential substance use disorder (SUD) treatment programs. Issue 1 (2nd January 2020) - Guydish, Joseph; Wahleithner, Jennifer; Williams, Denise; Yip, Deborah
Abstract: Smoke-free laws and policies have contributed significantly to the decline in smoking in the U.S, but are not often applied in high-prevalence smoking populations where they are most needed. Smoking among clients in publicly funded substance use disorder (SUD) treatment is 3-4 times higher than the general population, and little is known about tobacco policies programs have adopted. To identify the prevalence of tobacco-free grounds and other smoking policies in California's publicly funded, adult, residential SUD programs. Using a California DHCS contact list of 1, 921 publicly funded, non-medical, SUD programs, 362 were eligible to participate in a brief semi-structured phone survey concerning indoor and outdoor smoking for staff and clients and other tobacco policies. Of 259 programs that completed the survey, 28 (10.8%) reported tobacco-free grounds. 91 (35.1%) expressed interest in implementing tobacco-free policies and 23 have plans to do so. Nearly all programs (n = 253, 97.7%) had some policy restricting e-cigarette use, and 110 (43.5%) of these reported a complete ban on e-cigarette use. 124 (47.9%) had policies prohibiting staff and clients smoking together. Most California residential SUD programs allow outdoor smoking for staff and clients and few have adopted tobacco-free grounds policies. Given the reported interest in adopting tobacco-free policies, the high density of smokers in the SUD population, and the association of tobacco-free policies with lower client and staff smoking rates, state licensing and regulatory agencies, as well as county health departments, should work with SUD programs to adopt tobacco-free policies.